Young Plasma Rejuvenates Blood DNA Methylation Profile, Extends Mean Lifespan, and Improves Physical Appearance in Old Rats - Chiavellini, Priscila (2024)
There is converging evidence that young blood conveys cells, vesicles, and molecules able to revitalize function and restore organ integrity in old individuals. We assessed the effects of young plasma on the lifespan, epigenetic age, and healthspan of old female rats. Beginning at 25.6 months of age, a group of 9 rats (group T) was intraperitoneally injected with plasma from young rats until their natural death. A group of 8 control rats of the same age received no treatment (group C). Blood samples were collected every other week. Survival curves showed that from age 26 to 30 months, none of the group T animals died, whereas the survival curve of group C rats began to decline at age 26 months. Blood DNAm age versus chronological age showed that DNAm age in young animals increased faster than chronological age, then slowed down, entering a plateau after 27 months. The DNAm age of the treated rats fell below the DNAm age of controls and, in numerical terms, remained consistently lower until natural death. When rats were grouped according to the similarities in their differential blood DNA methylation profile, samples from the treated and control rats clustered in separate groups. Analysis of promoter differential methylation in genes involved in systemic regulatory activities revealed specific GO term enrichment related to the insulin-like factors pathways as well as to cytokines and chemokines associated with immune and homeostatic functions. We conclude that young plasma therapy may constitute a natural, noninvasive intervention for epigenetic rejuvenation and health enhancement.